(untitled) (Emancipação, 2022)
Regional journalism has its own characteristics. These peculiarities implicate from location until the content. The work we carried out was concerned with identifying the news media in the interior of the State of Paraná, notably the printed media (newspapers and magazines) and digital media (news portals and blogs) in the period 2018-2019. A survey allowed to know where each media is located in the State of Paraná and, therefore, trace a digital map of access to each of the media initiatives. The map allows you to view the concentration of news media in certain places, as well as the media absence that still exist. The crossing of data such as location, IDH, degree of urbanization, PIB and others, lets discuss why the media journalistic are in certain places and not in others.